Frequency Dependence of Q-Factor and Optimal Inductance for Pot Core Inductors - Jankovskis, J.; Yurshevich, V. (Elektronika ir Elektrotechnika, 2000)
Analytic relation for small signal frequency dependence of quality factor Q for pot core inductors is derived in terms of account for magnetic and copper loss and geometry of inductor. This relation allows to estimate the inductance value and the inductor size which for given frequency can be realised with maximum quality factor. Analysis performed reveals that influence of inductor size on quality factor depends on frequency: quality factor is proportional to quadrate of size for frequencies , proportional to size at and independent for .